ETHNOCULTURAL KNOWLEDGE AS A FACTOR FOR FORMING INTERNATIONAL TOLERANCE - Tangirov Eldor Sayfullayevich (Journals Park Publishing, 2022)
The article describes the definition of effective pedagogical conditions for the education of ethno-cultural tolerance of students in the process of theoretical education and practical pedagogical analysis. Due to the specific nature of the research, problems are used, including general scientific methods (comparison, systematization, scientific-terminological analysis and generalization). A wide range of pedagogical conditions of education is presented.
Keywords: tolerance; political; correctness